Experiencing algebra - Thomasson, JoAnne (Prentice Hall, 1999)
"Experiencing Algebra" combines beginning and intermediate algebra concepts and actively involves readers in a " total algebra experience." Thomasson and Pesut integrate the use of technology (assuming no prior graphing calculator skills on the part of readers); allow readers to experience algebra through discovery and visualization; illustrate multiple approaches (numerical, graphical, algebraic, and verbal) to problem solving. Rational Numbers; Real Numbers; Variables, Expressions, Equations, and Formulas; Relations, Functions, and Graphs; Linear Equations in One Variable; Linear Equations and Functions in Two Variables; Systems of Linear Equations in Two Variables; Inequalities; Polynomial Functions; Working with Polynomial Expressions; Polynomial Equations and Inequalities in One Variable; Rational Expressions, Functions, and Equations; Radical Expressions, Expressions Containing Rational Exponents, Functions, and Equations; Complex Numbers; Exponential and Logarithmic Functions and Equations.